Uma investigação sobre a ocorrência de viés de seleção amostral em concursos públicos no Brasil - Bezerra, Anderson Passos (2012)
The objective of this paper turns to evaluation of the factor that may influence the chances of approval in an aptitude test for admission in public jobs. Using a database obtained from a aptitude test realized by the Banco do Nordeste do Brasil, occurred in 2003 to mid-level positions, and from Pesquisa Nacional por Amostra de Domicílio (PNAD) database, also 2003, sought to draw a map of the determinats to approval in the aptitude test, however the hypothesis of sample selection occurrence was raised, since the enrollment process in the aptitude test was coupled with certain socioeconomic characteristics needing so, be considered in the analysis of the approval factors, or in other way, we could obtain biased results, if the problem (sample selection) occurs. To obtain success in our demand, we use an adaptation of the methodology proposed by Heckman, with an addition that was employed in a discrete choice model, because ours dependent variables are dummies, being to the enrollment process, if he enrolls or not and for the aptitude process, if he has succeeded or not. We estimated three models, being two models, considering the sample selection problem, and another without the selectivity. The results found pointed to nonexistence of the selectivity problem, confirming other papers on the same theme.